The carrot and the stick: Bank bailouts and the disciplining role of board appointments - Christian Mücke; Loriana Pelizzon; Vincenzo Pezone; Anjan V. Thakor (Leibniz Institute for Financial Research SAFE, 2021)
We empirically examine the Capital Purchase Program (CPP) used by the US government to bail out distressed banks with equity infusions during the Great Recession. We find strong evidence that a feature of the CPP - the government's ability to appoint independent directors on the board of an assisted bank that missed six dividend payments to the Treasury - helped attenuate bailout-related moral hazard. Banks were averse to these appointments - the empirical distribution of missed payments exhibits a sharp discontinuity at five. Director appointments by the Treasury led to improved bank performance, lower CEO pay, and higher stock market valuations.
Keywords: G01; G2; G28; G38; H81; 330; Bank Bailout; TARP; Capital Purchase Program; Dividend Payments; Board Appointments; Bank Recapitalization